A photochemical approach for a fast and self-limited covalent modification of surface supported graphene with photoactive dyes. - Fleischer, Karsten; Walls, Brian; Shvets, Igor; Sergeeva, Natalia N.; Chaika, Alexander N.; Walls, Brian; Murphy, Barry E.; Walshe, Killian; Martin, David P.; Richards, Billy D.O.; Jose, Gin; Aristov, Victor Yu.; et al. (My University, 2018)
Herein, we report a simple method for a covalent modification of surface supported graphene with photoactive dyes. Graphene was fabricated on cubic-SiC/Si(001) wafers due to their low cost and suitability for mass-production of continuous graphene fit for electronic applications on millimetre scale. Functionalisation of the graphene surface was carried out in solution via white light induced photochemical generation of phenazine radicals from phenazine diazonium salt. The resulting covalently bonded phenazine-graphene hybrid structure was characterised by scanning tunnelling microscopy (STM) and spectroscopy (STS), Raman spectroscopy and density functional theory (DFT) calculations. It was found that phenazine molecules form an overlayer, which exhibit a short range order with a rectangular unit cell on the graphene surface. DFT calculations based on STM results reveal that molecules are standing up in the overlayer with the maximum coverage of 0.25 molecules per graphene unit cell. Raman spectroscopy and STM results show that the growth is limited to one monolayer of standing molecules. STS reveals that the phenazine-graphene hybrid structure has a band gap of 0.8 eV.
PUBLISHED
Keywords: Graphene; Covalent functionalisation; Dyes; Photochemistry; Scanning tunnelling microscopy; Density functional theory